ANALISIS TREND JUMLAH KUNJUNGAN PASIEN SAAT PANDEMI DENGAN METODE TREND KUADRAT TERKECIL DI RUMAH SAKIT PANTI WILASA DR. CIPTO SEMARANG - Destri Maya Rani; Bajeng Nurul Widyaningrum; Nurul Hasanah (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2021)
Hospital statistics are statistics sourced from medical record data, as health information that will later be used to gain capacity for health practitioners, management, and medical personnel in decision making. Medical records and hospital statistics have a very close relationship, because hospital statistics are obtained from medical record data. Statistical indicators for outpatient units are data on daily patient visits, new patient visits and old patient visits. This type of research is a descriptive study with a quantitative approach. The research variable is the number of outpatient visits before the pandemic and during the pandemic in 2020, while the sample is outpatient data at the Panti Wilasa Hospital "Dr.Cipto" Semarang. the number of outpatient visits in 2020 increased by 25,4% or 60.330 patients with an average of 886 patient visits per day. from the calculations that have been done, the number of outpatient visits during the pandemic has increased